the Effect of Implementation of Discharge Planning with Family Centered Nursing Approach to Drug Compliance Level of Anti Hypertension Drugs in Elderly at Ulin Banjarmasin Hospital - candra kusuma negara; abd basid (CNJ: Caring Nursing Journal, 2018)
ABSTRACT Elderly is a natural process of growing flowers, elderly tend to experience health problems resulting from decreased body function due to aging process one of the effects of blood pressure lability occur. High blood pressure is a chronic disease that can not heal, can only be controlled by way of obedience to take anti-hypertensive drugs. There are several models of nursing concept one family centered nursing that is family model of caring for the family. This research is an experimental research included in quantitative research method with Quasi Eksperiment design. This research uses pre-test and post-test with control group design, and uses questionnaires to measure compliance and family roles. The questionnaire has met the requirements of the validity and reliability test. Of the 20 respondents, there were 14 (70%) female respondents and 6 (30%) male responder. A total of 15 (75%) respondents were aged 60-70 years, 5 (25%) responder was> 70 years old. The average test result of two samples in experimental group of mean result is 15,20 with std value. deviation 3.047, for the control group value is known the mean value of 15.20 std value. deviation 4,458 with t-count value is 0,059 and obtained value p value is at 0,02 this value <from p value 0,05 meaning Ha accepted which mean there is difference of mean between two samples. These results indicate that there is Influence of Implementation of Discharge Planning with Family Centered Nursing Approach to Drug Compliance Level of Anti Hypertension Drug at elderly in Ulin Banjarmasin Hospital.